Reforesting Landscapes Linking Pattern and Process - Nagendra, Harini; Southworth, Jane (Landscape Series, 2010)
The 21st century has seen the beginnings of a great restoration effort towards the world's forests, accompanied by the emergence of an increasing literature on reforestation, regeneration and regrowth of forest cover. Yet to date, there is no volume which synthesises current knowledge on the extent, trends, patterns and drivers of reforestation. This edited volume draws together research from leading researchers to explore reforestation and forest regrowth across the world, from multiple dimensions - including ecosystem services, protected areas, social institutions, economic transitions, remediation of environmental problems, conservation and land abandonment - and at different scales. Detailing the methods and analyses used from across a wide range of disciplines, and incorporating research from North, South and Central America, Africa, Asia and Europe, this groundbreaking book provides a global overview of current trends, explores their underlying causes and proposes future forest trajectories. The first of its kind, the book will provide an invaluable reference for researchers and students involved in interdisciplinary research and working on issues relevant to the biophysical, geographic, socioeconomic and institutional processes associated with reforestation.